Diagnostic Performance of Endoscopic and Microscopic Procedures for Identifying Different Middle Ear Structures and Remaining Disease in Patients with Chronic Otitis Media: A Prospective Cohort Study. - Farhad Farahani; Elnaz Shariatpanahi; Javane Jahanshahi; Jalal Poorolajal (PLoS ONE, 2015)
BACKGROUND:The diagnostic performance of endoscopic and microscopic procedures for detecting diseases of the middle ear in patients with chronic otitis media (COM) has rarely been investigated. This study was conducted to compare the performance of these procedures for identifying middle ear structures and their associated diseases in COM patients. METHODS:In this prospective cohort study, 58 patients with chronic COM, who were candidates for tympanoplasty with or without a mastoidectomy, were enrolled. Before the surgical intervention, the middle ear was examined via an operating microscope and then through an endoscope to identify the middle ear structures as well as diseases associated with the middle ear. RESULTS:The patients were 15 years of age or older. The anatomical parts of the middle ear - the epitympanic, posterior mesotympanic, and hypotympanic structures - were more visible through an endoscope than through a microscope. In addition, the various segments of the mesotympanum, oval window, round window, and Eustachian tube were more visible via endoscopy. The post-operative endoscopic reevaluation of the middle ear revealed that a cholesteatoma had remained in four of 13 patients after surgery. CONCLUSION:According to the results of this study, in cases in which there is poor visibility with the operating microscope or the surgeon suspects remaining disease within the middle ear, endoscopy could be utilized to improve the evaluation of more hidden middle ear pits and structures, particularly if there is a potentially recrudescent pathology.